ÍNDICE DE CAMINHABILIDADE: APLICAÇÃO EM UMA CIDADE MÉDIA BRASILEIRA - Leão, Ana Luiza Favarão; Olak, André Silva; Kanashiro, Milena (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
According to the World Health Organization, non-communicable diseases represent a threat to human development and the susceptibility to them increases due to physical inactivity (WORLD HEALTH ORGANIZATION, 2015). In this scenario, walking has been identified as a daily way to promote physical activity (LIN; MOUDON, 2010), accessibly and with low cost (DOESCHER et al., 2014). Experimental evidence has identified direct environmental influence as a stronger determinant of walking behaviors than cognitively mediated behavioral choices (OWEN et al., 2004).. Walkability can be measured through objective and perceived means. This paper aims to verify the applicability of an objective measure of the built environment the walkability index developed by Frank et al. (2010), in a medium-sized Brazilian town. This method systematizes four variables: residential density, land use mix, intersection density and retail floor area ratio in an effort to analyze walkability. In this study, walkability was quantified in quartiles and pointed out limitations imposed by the scale and geographical formation of local administrative units. This study contributes to the redefining of objective walkability measures, forwarding a strategy to analyze active mobility in medium-sized Brazilian towns.